First Autologous Cord Blood Therapy for Pediatric Ischemic Stroke and Cerebral Palsy Caused by Cephalic Molding during Birth: Individual Treatment with Mononuclear Cells - A. Jensen; E. Hamelmann (Case Reports in Transplantation)
Intracranial laceration due to traumatic birth injury is an extremely rare event affecting approximately one newborn per a population of 4.5 million. However, depending on the mode of injury, the resulting brain damage may lead to lifelong sequelae, for example, cerebral palsy for which there is no cure at present. Here we report a rare case of neonatal arterial ischemic stroke and cerebral palsy caused by fetal traumatic molding and parietal depression of the head during delivery caused by functional cephalopelvic disproportion due to a “long pelvis.” This patient was treated by autologous cord blood mononuclear cells (45.8 mL, cryopreserved, TNC 2.53×10e8) with a remarkable recovery. Active rehabilitation was provided weekly. Follow-up examinations were at 3, 18, 34, and 57 months. Generous use of neonatal head MRI in case of molding, craniofacial deformity, and a sentinel event during parturition is advocated to enhance diagnosis of neonatal brain damage as a basis for fast and potentially causative treatment modalities including autologous cord blood transplantation in a timely manner.